PENTINGNYA PEMENUHAN GIZI PADA CALON PENGANTIN DALAM RANGKA MEMPERSIAPKAN KEHAMILAN SEHAT - Handayani, Ririn; Handayani, Yuni; Zalika, Laila Karimatu; Putri, Meyla Eka (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2022)
Premarital check up merupakan serangkaian tes yang harus dilakukan oleh setiap pasangan calon pengantin. Premarital check up terdiri atas Pemeriksaan fisik secara umum, Persiapan gizi calon pengantin, Skrining status TT, Pemeriksaan kesehatan organ reproduksi, Pemeriksaan darah, Pemeriksaan urin, Pemeriksaan IMS. Kegiatan kelas pranikah dan pemeriksaan kesehatan pranikah dapat dilakukan disarana kesehatan layanan primer yaitu Puskesmas. Premarital check up penting dilakukan bagi calon pengantin untuk melihat kondisi kesehatannya guna mempersiapkan kehamilan sehat dan untuk memperoleh keturunan yang sehat. Tujuan penelitian ini adalah untuk meningkatkan pengetahuan calon pengantin tentang Pentingnya Pemenuhan Gizi Pada Calon Pengantin Dalam Rangka Mempersiapkan Kehamilan Sehat. Premarital check-up is a series of tests that must be carried out by every bride and groom. Premarital check-up consists of general physical examination, nutritional preparation of the prospective bride and groom, TT status screening, reproductive organ health examination, blood examination, urine examination, IMS examination. Premarital class activities and premarital health checks can be carried out in primary health care facilities, namely Puskesmas. Premarital check-up is important for the bride and groom to see their health condition in order to prepare for a healthy pregnancy and to produce healthy offspring. The purpose of this study was to increase the knowledge of prospective brides about the importance of nutrition for brides and grooms in preparing for a healthy pregnancy. This community service activity is carried out to all prospective bride and groom couples at KUA Kaliwates. The method of delivering health education is done by question and answer discussion to all respondents. The results of community service activities have been providing education to prospective brides through lectures, distribution of reproductive health pocket books, discussions about the importance of fulfilling nutrition for brides and grooms. The responses generated by the respondents were enthusiastic enough to be understood by the bride to be. This is evidenced by the existence of questions and answers from respondents. Anthropometric examination has been carried out on the prospective bride including weight, height, lila. From the results of the examination all targets were within normal limits. The hemoglobin level has been checked using an electric detector. The results of the Hb examination of all targets were 5 people with mild anemia and 45 normal people. The distribution of blood-added tablets to all targets has been carried out with 10 tablets each to be taken 1 tablet every day